A note on the teaching of ethics in the MBA macroeconomics course - Abell, John D. (Journal of business ethics, 1990)
While there is general agreement on the need to teach ethics in the MBA classroom, there are great difficulties in completely integrating such material within the confines of an actual MBA program. This paper attempts to address these difficulties by focusing on the teaching of such issues in one particular class — MBA macroeconomics., Ethical dilemmas often arise due to failures of the market place or due to inappropriate assumptions regarding the market model. Thus, specific suggestions are offered in regard to the integration of ethical issues into the traditional macroeconomic curriculum. Suggestions are even offered as how to scale back the basic macro material so that the additional material may be accommodated., In addition to fulfilling the mandate to develop a well educated citizenry with regard to issues of ethics and economics, the course may be structured so as to emphasize writing skills, speaking skills, and critical analytical thinking skills.